Multiple cytokines sharing the common receptor γ chain can induce CD154/CD40 ligand expression by human CD4(+) T lymphocytes via a cyclosporin A-resistant pathway - Fayen, John D (Blackwell Science Inc, 2001)
Expression of CD154/CD40 ligand (CD154/CD40L), an important molecular component of CD4(+) T-cell help, can be triggered by T-cell receptor (TCR) stimulation. Dephosphorylation of the transcriptional element Nuclear Factor of Activated T cells-1 (NFAT1) is a critical activation step in the TCR-initiated signal transduction cascade which promotes CD154/CD40L expression. Cyclosporin A (CsA), which interferes with NFAT1 activation, has been shown to be an effective inhibitor of TCR-triggered CD154/CD40L expression by resting T cells. We now report that recombinant interleukin-2 (rIL-2) is also capable of inducing CD154/CD40L on CD4(+) T lymphoblasts via a pathway triggered independently of the CD3/TCR receptor complex. Recombinant IL-2-mediated CD154/CD40L expression, in contrast to that triggered by CD3/TCR stimulation, is only partially inhibited by CsA. The capacity of rIL-2 to induce CD154/CD40L expression by T lymphoblasts also extends to a restricted number of cytokines sharing the cytokine receptor common γ chain, including IL-15, and, to a lesser extent, IL-7, but not IL-4. A similar CsA-resistant CD154/CD40L induction pathway can be triggered in primary T cells by the combination of anti-CD3 stimulation and recombinant lymphokines. In contrast to T lymphoblasts, the CsA-resistant CD154/CD40L induction in primary lymphocytes can be efficiently triggered by multiple cytokines which bind the common γ chain receptor family. The data outline a novel pathway of CD154/CD40L induction which is, at least in part, independent of NFAT1 and resistant to CsA. A more complete understanding of the mechanisms governing CD154/CD40L expression may facilitate the rational design of specifically targeted immunotherapeutic agents.